lntercambiador de transporte Santa Rosa - Sevilla-Medina, Agnes (Instituto Tecnológico de Costa Rica., 2019)
Within the Carbon Neutrality Objectives 2019 - 2050, the optimization of transport schemes influences the reduction of greenhouse gas emissions, which is why the mobility plans made by national institutions seek a modernization of public transport through the implementation of facilities that allow active and sustainable mobility as infrastructures that provide security and comfort to users. The objective of this project is to design a public transport interchange station that promotes sustainable mobility through the integration of active and motorized mobility means in an infrastructure integrated to its environment and that provides spaces for social convergence. To achieve this, a study was carried out on the theme of sustainable mobility, as well as related plans and projects, current demands and variables to consider. The project was developed under the mobility criteria of the PRUGAM plans (2008), Plan GAM 2013, Sectorization and Modernization of Public Transport of the Metropolitan Area of San José (2018), also under the regulations of the Municipality of Santo Domingo, as well as the demands imposed by Incofer on the implementation of the Rapid Passenger Transport in the Greater Metropolitan Area. Finally, the project is complemented with the application of good mobility practices obtained from the research process of the subject and the study of the context where it was implemented in order to generate a contribution to the solution of mobility problems in the area.
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2019
Keywords: Costa Rica, Santa Rosa de Santo Domingo; Transporte urbano; Transporte público; Planeamiento urbano